Tanaidaceans (Crustacea: Malacostraca: Peracarida) from soft-sediment habitats off Israel, Eastern Mediterranean - Bamber, Roger N; Bird, Graham; Błażewicz-Paszkowycz, Magdalena; Galil, Bella (Zootaxa, 2009)
Tanaidacean material collected by the Israel Oceanographic and Limnological Research (IOLR) surveys between 2005 and 2007, in the Levant Sea off the coast of Israel, has been studied. A total of 21,731 individuals representing 15 species and 11 genera was identified from 351 samples. Of the eight species of Apseudomorpha, one, a species of Leviapseudes, is new to the Mediterranean, and probably to science, but the damaged immature material precludes description and diagnosis. The continued presence in this region of the Erythrean species Cristapseudes omercooperi was confirmed. Of the seven species of Tanaidomorpha, five are previously undescribed species, one each in the genera Akanthophoreus, Leptochelia, Pseudotanais, Typhlotanais and Tanaissus, the last being the commonest tanaidacean in the samples, yet the first record of the genus for the Mediterranean.